Ruptured ulnar artery aneurysm in vascular Ehlers-Danlos syndrome - Howard, Ryan (J Vasc Surg Cases Innov Tech, 2020)
Vascular Ehlers-Danlos syndrome (vEDS), also known as type IV Ehlers-Danlos syndrome, is a rare inherited connective tissue disease that affects 1 in 50,000 to 250,000 individuals. It is characterized by catastrophic vascular complications and hollow viscus rupture; 80% of patients with vEDS experience a vascular complication by the age of 40 years, and median life expectancy is 40 to 50 years. The central vasculature and visceral vasculature are most commonly affected; peripheral involvement is much less common. We describe the case of a 40-year-old woman with vEDS previously complicated by ruptured splenic and posterior tibial artery aneurysms who presented with a ruptured left ulnar artery aneurysm resulting in compartment syndrome.